2004
DOI: 10.1002/ab.20052
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive encounters between patients and general hospital staff: Staff perceptions of the context and assailants' levels of cognitive processing

Abstract: A considerable body of research has accumulated regarding aggression toward health care staff, yet little is known about the contextual factors involved. The present study examined the context within which aggressive incidents occurred and the dynamics of the interaction between staff and patients. Two aspects in particular were investigated; firstly, whether incidents were preceded by some anxiety provoking stimulus and secondly, the assailants' levels of cognitive processing apparent at the time of the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 14 publications
2
48
0
1
Order By: Relevance
“…Overall attitude, including tone, negativity and confronting and questioning patients' validity for presenting to the ED, for example, can initiate or exacerbate acts of violence. 1,34 Education for ED staff should focus on effective verbal and non-verbal communication, as well as recognition of potential for violence, and de-escalation strategies including negotiation skills. 24,31 Education should also promote a culture of workplace safety, in which reporting workplace violence is encouraged and feedback provided.…”
Section: Education Of Staffmentioning
confidence: 99%
“…Overall attitude, including tone, negativity and confronting and questioning patients' validity for presenting to the ED, for example, can initiate or exacerbate acts of violence. 1,34 Education for ED staff should focus on effective verbal and non-verbal communication, as well as recognition of potential for violence, and de-escalation strategies including negotiation skills. 24,31 Education should also promote a culture of workplace safety, in which reporting workplace violence is encouraged and feedback provided.…”
Section: Education Of Staffmentioning
confidence: 99%
“…In most cases, patients and their relatives found it difficult to find doctors (42.3%) who would listen to them (Table 2). Furthermore, 13.3% o f the respondents partly or completely be lieved that the intervening doctor should be beaten or killed when a patient died. A total of 67.4% of the respondents were disturbed after receiving news that healthcare staff had been subjected to violence, with 14.3% being directly or indirectly pleased.…”
Section: Resultsmentioning
confidence: 99%
“…A majority o f the vic tims o f violence are general practitioners (67.6%) and nurses (58.4%) (7), and acts of violence in the health sector are primarily observed in emergency departments (8)(9)(10). Among the factors increasing the risk of violence are 24-h non-stop service; stressed family mem bers; prolonged waiting times (11,12); too many examinations and tests (8); personality traits of patients (13,14), nurses (15)(16)(17), other healthcare staff, and patients' relatives (18,19); relatively low num ber of personnel to address an intensive workload; working in a very crowded environment; lack of education in addressing violence; in adequate number o f security personnel; and lack of any restrictions on violence in health center regulations (5). Although society gener ally disapproves of acts o f violence, it does not do much to alleviate the suffering of the healthcare staff exposed to acute violence and offers relatively little support (18%) for their suffering (20).…”
Section: Introductionmentioning
confidence: 99%
“…Hahn, in a review regarding patient and visitor violence in general hospitals found that between 3 and 58% of physicians are aggressed per year. 24 The main reasons for the aggressive behavior are: the cultural context, first two or three days after admission, 25 increased waiting times, 2 admission in a public, general hospital, 25 night shifts, 26 understanding difficulties regarding medical problems, 26,27 unavailability of the physician, 27 difficult discharge procedures, 27 women and child care, 27 enforced personal care or medical treatment, 27 anger directed towards hospital rules and regulations, 28 etc.…”
Section: Discussionmentioning
confidence: 99%
“…The physicians in training are more exposed to this phenomenon due to: a defective training in violence management, 36 inadequacies regarding the identification of violent and pre-violent acts and behaviors, 35 difficulties in directing their attention to the anxiety and fears aroused when dealing with a violent patient, 37 difficulties in identifying the needs of patients with violent behaviors, the misconception that residens must "suck it up" (abuse and harassment is considered part of the job), 4 difficulties in reporting harassment/abuse, or not knowing where to go to report it, 4 fear of reprisal, 4 misconception that nothing can be done to minimize this phenomenon. 4 Differences between the aggressive acts in different specialties depends mainly upon the particularities of the patients and their medical conditions 24 ; however there are other causes that may influence the frequency of violent behavior, amongst which are cited: alcohol drinking (increased aggressiveness), often present in the ER, type of institution (for example university clinics are significantly less exposed to physical aggression compared to general hospitals), 38 aggressive behaviors from the superiors that increase irritability and stress, and therefore diminish the capacity to interact with the patient, 38,39 the severity of the disease, 2 type of medical care, 27,40 type and nature of the contact with the patients 28,41 , 24 . In our study psychiatry trainees are also put at a high risk, especially by patients with acute disorders.…”
Section: Discussionmentioning
confidence: 99%